Expanded Newborn Screening in Italy: The First Report of Lombardy Region - Clarissa Berardo; Alessandra Vasco; Alessia Mauri; Simona Lucchi; Laura Cappelletti; Laura Saielli; Manuela Rizzetto; Davide Biganzoli; Cristina Montrasio; Diana Postorivo; Elisa Pratiffi; Andrea Meta; et al. (International Journal of Neonatal Screening)
Background: Newborn screening (NBS) is a preventive healthcare program aiming at identifying the inborn errors of metabolism (IEMs) in asymptomatic infants to reduce the risk of severe complications. The aim of this study was to report the first years (2016–2020) of the expanded NBS program in the Lombardy region, Italy. Methods: Dried blood spots were collected from newborns’ heels at 48–72 h after birth. FIA-MS/MS was performed to evaluate specific biochemical markers. Genetic confirmation was achieved via Sanger or NGS on newborns and reported to a clinical reference center (CRC). Results: A total of 343,507 newborns were tested; 1414/343,507 resulted as positive to NBS and were reported to the CRC. A total of 209 newborns were diagnosed with IEMs: 206 infants received a diagnosis of IEM through NBS, confirmed by genetic analysis; three neonates were not positive to NBS but were subsequentially diagnosed with IEMs. A total of 1208/343,507 were false positive cases. Twenty-seven types of IEMs were diagnosed in 209 patients: 111 newborns were affected by aminoacidemias, 11 by urea cycle disorders, 27 by organic acidemias, 34 by fatty acid oxidation disorders, and 26 by secondary conditions. Conclusions: We report here for the first time the IEM incidence and distribution in the Lombardy region in the first five years of NBS.